Spatial patterns of dominant bacterial community components and their influential factors in the southern Qinling Mountains, China - Zhao, Yonghua; Luo, Manya; Zhou, Yujie; Jia, Xia; Kang, Shuaizhi; Yang, Shuyuan; Mu, Qi (Frontiers in Microbiology, 2022)
Soil bacteria not only maintain the biodiversity of forest ecosystems but also affect soil nutrient cycling and ecosystem function. Nonetheless, the spatial distribution pattern of dominant bacterial community components in soil are still rarely explored. Therefore, the spatial distribution pattern of the dominant bacterial community components and their influential factors were investigated using traditional statistics, geostatistics and kriging spatial interpolation methods in the Huoditang region of the Qinling Mountains, China. The results showed that the dominant bacterial phyla were Proteobacteria, Acidobacteria, Chloroflexi, Rokubacteria, Actinobacteria and Verrucomicrobia in this region. Among the bacterial phyla, Proteobacteria occupied an area of 2.56 km2 (the greatest) in the highest patch category, followed by Planctomycetes. Moreover, among the lowest patch category, Firmicutes occupied the lowest area (11.93 km2). The results of kriging maps showed that the dominant bacterial community components presented “peak”, “bimodal”, and “multimodal” distributions in Huoditang. Proteobacteria, Acidobacteria, Chloroflexi, Gemmatimonadetes, Nitrospirae and ASV (amplicon sequence variants) had significant spatial autocorrelation (< 0.68 km). Variance partitioning analysis confirmed that soil nutrients (36.5%) were the significant driving factors shaping the bacterial community structure, followed by environmental factors (28.2%) and topographic factors (7.8%). Furthermore, pH (9.1%), soil organic carbon (SOC, 6.6%), available phosphorus (AP, 4.7%) and elevation (3.9%) were the most important driving factors for the spatial distribution of bacterial community in the Huoditang Forest of the Qinling Mountains. The findings provide a new perspective for studying the spatial distribution characteristics and driving factors of dominant soil bacterial community components in subtropical forest ecosystems.